Seasonal orientation of solar collectors for the philippines - Saiful Bari (Universitas Gadjah Mada, 2001)
In this paper, a method to determine the slope angle for seasonal applications of flat plate collectors is described for the Philippines territory. For seasonal applications, where the collectors are used only for a fraction of the year, the slope angles need to be different from those for year-round operations. For year-round operations, most flat collectors are usually fixed, and mounted at an angle equal to the latitude tilt angle. The method described here utilized both direct and diffuse components of solar radiation, and air mass using average atmosphere. For seasonal applications of solar energy such as crop drying, the optimum slope angle can be found conveniently and accurately by this method